Analysis and Estimation of Key Risks of Bank System in Russia and their Impact on Banking Sector in Conditions of Macro-Economic Instability - A. V. Kvitsinia (Вестник Российского экономического университета имени Г. В. Плеханова, 2025)
The article analyzed credit risk at all banks of the Russian Federation, except non-bank credit organizations and drew a conclusion about maintaining finance stability of big business representatives and moderate level of debt liabilities. It describes possible negative impact of economic factors on solvency of borrowers that could affect the risk of credit portfolio in the future. Special attention is paid to consequences of oil price fluctuations and changes in the ruble rate, which can cause structural deficit of liquidity and ruble crash. Steps taken by the government and the Bank of Russia were discussed that are aimed at struggle with foreign currency risk, including balancing of transition to national currencies. And finally an adaptive model was put forward that could provide more precise and reliable estimation of credit risk. Certain steps aimed at minimizing liquidity and foreign currency risks were advanced.